2021
DOI: 10.18332/ejm/138595
|View full text |Cite
|
Sign up to set email alerts
|

Adherence and Associated Factors to Iron and Folic Acid Supplementation Among Pregnant Women Attending Antenatal Care in Public Hospitals of Dire Dawa, Eastern Ethiopia

Abstract: INTRODUCTION Worldwide, 41.8% of pregnant women have anemia. Nationally, only 0.4% of pregnant women take the recommended 180-day iron supplement for more than 90 days. This study aimed to determine adherence to iron and folic acid supplements and factors affecting it among pregnant women attending antenatal care in public hospitals of Dire Dawa City, eastern Ethiopia. METHODS An institutional-based cross-sectional study design was conducted from 1 January 2019 to 30 Ju… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
22
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 22 publications
4
22
4
Order By: Relevance
“…In this study, the overall compliance rate of iron supplementation during pregnancy was found to be 92.4%. The current finding was higher than many previous reports in Ethiopia, such as the compliance rate, which varied from 60 to 63.6% in Addis Ababa 32 , 44 , 45 , 87.6% in Ethiopia 37 , Dire Dawa 46 , Shalla District 47 , 43.4% Dilla town 48 , 38.3% Hadassah 28 , 51.4% Burin district 49 , 52.9% Debbie 50 , 28.1% Denbiya District 36 , 28.7% Lay Armachiho 31 , 55% Gondar 51 , 47.6% Aykal town 30 , 44% Debre Tabor 52 , 43% Wollo 53 and 74.9% in four regions of Ethiopia 20 , 67.6% Simada district 54 , 52.8% Debay Tilat Gen district 55 , 37.2% Northwestern zone of Ethiopia 35 , 55.5% Debre Markos town 56 , 76.9% Dangila, Northern Ethiopia 57 , 40.9% in Adwa town 58 , and meta-analyses, 46.15, 46.1, 41.38 and 43.63% 59 62 . The present finding was also higher than many others, for example, a meta-analysis in SSA 63 , Uganda 64 , Kenya 65 , Nigeria 24 , Northwest Tanzania 66 , Northern Tanzania 67 , 22 sub-Saharan African countries 23 , Niger 68 , West Iran 69 , Cambodia 34 , Nepal 70 , 71 , India 72 , and Sri Lanka 73 .…”
Section: Discussioncontrasting
confidence: 84%
“…In this study, the overall compliance rate of iron supplementation during pregnancy was found to be 92.4%. The current finding was higher than many previous reports in Ethiopia, such as the compliance rate, which varied from 60 to 63.6% in Addis Ababa 32 , 44 , 45 , 87.6% in Ethiopia 37 , Dire Dawa 46 , Shalla District 47 , 43.4% Dilla town 48 , 38.3% Hadassah 28 , 51.4% Burin district 49 , 52.9% Debbie 50 , 28.1% Denbiya District 36 , 28.7% Lay Armachiho 31 , 55% Gondar 51 , 47.6% Aykal town 30 , 44% Debre Tabor 52 , 43% Wollo 53 and 74.9% in four regions of Ethiopia 20 , 67.6% Simada district 54 , 52.8% Debay Tilat Gen district 55 , 37.2% Northwestern zone of Ethiopia 35 , 55.5% Debre Markos town 56 , 76.9% Dangila, Northern Ethiopia 57 , 40.9% in Adwa town 58 , and meta-analyses, 46.15, 46.1, 41.38 and 43.63% 59 62 . The present finding was also higher than many others, for example, a meta-analysis in SSA 63 , Uganda 64 , Kenya 65 , Nigeria 24 , Northwest Tanzania 66 , Northern Tanzania 67 , 22 sub-Saharan African countries 23 , Niger 68 , West Iran 69 , Cambodia 34 , Nepal 70 , 71 , India 72 , and Sri Lanka 73 .…”
Section: Discussioncontrasting
confidence: 84%
“…Some studies have also reported higher levels of adherence to IFAS among women attending antenatal care. A study conducted among pregnant women attending antenatal care in public hospitals of Dire Dawa, Eastern Ethiopia reported an adherence level of 71.8% and a cross sectional study conducted in North West province, South Africa reported an adherence level of 93% [21,22]. The possible explanation in these studies include differences in study populations and the less strict criteria used to classify women as adherent or not.…”
Section: Adherence To Ifasmentioning
confidence: 99%
“…Iron supplementation is the best way of reducing iron deficiency anemia [ 6 ]. Pregnant mothers are advised to take iron supplementation for 180 days during pregnancy [ 7 ]. In addition to iron supplementation, pregnant women should be advised to eat foods high in iron and prevent intestinal worms [ 8 ].…”
Section: Introductionmentioning
confidence: 99%